An Update on Pediatric Alopecia Areata (Canadian Dermatology Today, 2021)
Alopecia Areata (AA) is a common, non-scarring autoimmune alopecia affecting both children and adults. AA is the third most common dermatosis in children and has a significant emotional impact on patients, particularly children. At present, there are no universally effective treatments that guarantee low relapse rates or complete regrowth in severe disease. There is a lack of data for treatment of pediatric alopecia areata. This article provides an overview of pediatric alopecia areata and its management, including relevant peer-reviewed literature in the last 5 years.